PsycEXTRA Dataset 2011
DOI: 10.1037/e573292012-017
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Korean American First Born or Only Sons in the United States: Privilege or Burden?

Abstract: of the Dissertation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 31 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…Consistent with Asian culture’s emphasis on deference to parents and filial piety, research has demonstrated that parents play a significant role in AAs’ occupational choices (Kim, 2013; Loo, 2005; Qin, 2011; Roysircar, Carey, & Koroma, 2010). For example, AAs often reported experiencing parental pressure toward pursuing prestigious and high salary occupations (i.e., stereotypical occupations; Kim, 2013; Roysircar et al, 2010). They also indicated that parental support (e.g., financial and emotional support) had a significant yet distinct effect from parental pressure on their occupational choices (Fouad et al, 2008; Loo, 2005).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Consistent with Asian culture’s emphasis on deference to parents and filial piety, research has demonstrated that parents play a significant role in AAs’ occupational choices (Kim, 2013; Loo, 2005; Qin, 2011; Roysircar, Carey, & Koroma, 2010). For example, AAs often reported experiencing parental pressure toward pursuing prestigious and high salary occupations (i.e., stereotypical occupations; Kim, 2013; Roysircar et al, 2010). They also indicated that parental support (e.g., financial and emotional support) had a significant yet distinct effect from parental pressure on their occupational choices (Fouad et al, 2008; Loo, 2005).…”
mentioning
confidence: 98%
“…Among the life, physical, and social science occupations, AAs represent from 13.6% to 33.3% of biological, medical, and chemical or material scientists compared with only 3.2% of psychologists. Thus, AAs may be restricted in their range of occupational choices (Kim, 2013; Liu, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…"Special" status might, however, bring unique pressures and self-esteem needs as cautioned by Adler (1935) and others (Eckstein et al, 2010;Kim, 2013). Adjustment difficulties in response to perceived criticism, rejection, threat, or abuse might be magnified among firstborn or only children.…”
Section: Discussionmentioning
confidence: 92%
“…Kim (2013) recently concluded through a qualitative analysis that the firstborn "privileges" of Korean Americans were indeed tempered by the pressure of high expectations. A recent review of 200 birth order studies found evidence of firstborn traits such as dependence on the approval of others, vulnerability to stress, fearfulness in new situations, egocentricism, and disturbing dream content that might suggest higher relative difficulties in adapting to less-than-optimal developmental challenges (Eckstein et al, 2010).…”
Section: Firstborn Advantages and Vulnerabilities?mentioning
confidence: 98%